A CONDENSED APPROACH TO THE CYBER RESILIENT DESIGN SPACE. Issue 2 (July 2016) - Norman, Sharon; Chase, Justice; Goodwin, Daniel; Freeman, Bill; Boyle, Vern; Eckman, Rusty
ABSTRACT: In this paper, we describe cyber resiliency concepts, articulate models for where and how to design in resiliency, and provide examples of resiliency techniques. We describe the Continuous Trust Restoration concept and present "Start Secure. Stay Secure. Return Secure™" as three phases to consider when requiring, implementing, and deploying cyber resiliency. We have touched on the importance of metrics for verification and validation, and we have provided a few examples of cyber resiliency solutions and techniques that are relevant to software and systems. It is important for systems engineers to consider how cyber resiliency can affect their systems, if they need it, and how to incorporate it early in the design process.